Pengaruh Pajak Bumi Dan Bangunan Terhadap Pendapatan Asli Daerah Di Kabupaten Tolitoli Periode 2015-2020 (Bahasa Ingris) - Trisna (Jurnal Multidisiplin Madani, 2022)
The research used in this research is quantitative research. This study aims to explain the relationship between the independent variable and the dependent variable through the submission of hypotheses and to analyze how much influence the independent variable has on the dependent variable. The type of data used is secondary data sourced from reports on the realization and targets of PAD and PBB revenues at the Tolitoli BKD office. Data collection techniques using time series data with data analysis using simple linear regression. Based on the results of the research used, it can be concluded that the effect of the independent variable on the dependent or the effect of land and building taxes on local revenue in Tolitoli Regency, Central Sulawesi Province for the 2015-2020 period. With an R-square value of 61% and the remaining 39% influenced by other variables outside the study, for example the Cost of Acquisition of Land and Building Rights (BPHTB). This research is expected to be taken into consideration by the Tolitoli Regency Government to support effectiveness and efficiency in the management of Land and Building Taxes and Regional Original Revenues.